PARROT Ireland: Placental growth factor in Assessment of women with suspected pre-eclampsia to reduce maternal morbidity: a Stepped Wedge Cluster Randomised Control Trial Research Study Protocol. Issue 2 (1st March 2019) - Hayes-Ryan, Deirdre; Hemming, Karla; Breathnach, Fionnaula; Cotter, Amanda; Devane, Declan; Hunter, Alyson; McAuliffe, Fionnuala M; Morrison, John J; Murphy, Deirdre J; Khashan, Ali; McElroy, Brendan; Murphy, Aileen; et al.
Abstract : Introduction: Women presenting with suspected pre-eclampsia are currently triaged on the basis of hypertension and dipstick proteinuria. This may result in significant false positive and negative diagnoses resulting in increased morbidity or unnecessary intervention. Recent data suggest that placental growth factor testing may be a useful adjunct in the management of women presenting with preterm pre-eclampsia. The primary objective of this trial is to determine if the addition of placental growth factor testing to the current clinical assessment of women with suspected preterm pre-eclampsia, is beneficial for both mothers and babies. Methods and analysis: This is a multicentre, stepped wedge cluster, randomised trial aiming to recruit 4000 women presenting with symptoms suggestive of preterm pre-eclampsia between 20 and 36+6 weeks' gestation. The intervention of an unblinded point of care test, performed at enrolment, will quantify maternal levels of circulating plasma placental growth factor. The intervention will be rolled out sequentially, based on randomisation, in the seven largest maternity units on the island of Ireland. Primary outcome is a composite outcome of maternal morbidity (derived from the modified fullPIERS model). To ensure we are not reducing maternal morbidity at the expense of earlier delivery and worse neonatal outcomes, we have established a co-primary outcome which will examine the effect of the intervention on neonatal morbidity, assessed using a composite neonatal score. Secondary analyses will examine further clinical outcomes (such as mode of delivery, antenatal detection of growth restriction and use of antihypertensive agents) as well as a health economic analysis, of incorporation of placental growth factor testing into routine care. Ethics and dissemination: Ethical approval has been granted from each of the seven maternity hospitals involved in the trial. The results of the trial will be presented both nationally and internationally at conference and published in an international peer-reviewed journal. Trial registration number: NCT02881073 .